A STUDY ON WATER QUALITY OF RAW WATER SOURCES OF PDAM (MUNIPICAL WATER COMPANY) BANDARMASIH - Ulfa Fitriati; Novitasari Novitasari; Ellysa Eriyanie (TROPICAL WETLAND JOURNAL, 2015)
High demand for clean water in Banjarmasin requires PDAM Bandarmasih to do some developments, but its efforts are hindered by the water quality of raw water to be processed. It is therefore necessary to conduct a study on the water quality of raw water sources of PDAM Bandarmasih, especially during dry season. Water quality testing was carried out by performing direct experiments in the field and in the laboratory with 7 criteria including water temperature, electrical conductivity, total dissolved solids, pH, turbidity, salinity and dissolved oxygen that were compared with the criteria of water class B (water that can be used as the raw water for drinking water), on the basis of the Regulation of the Minister of Health of the Indonesia Republic No. 492/Menkes/PER/IV/2010. Based on the analyses of water quality in the field and in the laboratory from 4 intakes namely Sungai Tabuk, Pematang Panjang, Sungai Lulut and Sungai Bilu, and the comparison of the results with the test results of water quality of the samples from PDAM taken in dry season, indicated that the amount of salt content (salinity) in two intakes, Sungai Lulut and Sungai Bilu was so high that the production of clean water from both intakes was stopped temporarily during the dry season. The service for clean water was therefore provided only at the intakes of Sungai Tabuk and Pematang Panjang during dry season, resulting in some reduction in distribution to some areas in Banjarmasin.